Operator-Related Function Theory and Time-Frequency Analysis - Gröchenig, Karlheinz (Springer, 2015)
This book collects the proceedings of the 2012 Abel Symposium, held at the Norwegian Academy of Science and Letters, Oslo. The Symposium, and this book, are focused on two important fields of modern mathematical analysis: operator-related function theory and time-frequency analysis; and the profound interplay between them.